COPD in the Elderly Features of the Course, Treatment, Diagnosis, Management of Patients Age-Related Aspect - Kenzhaev O.O; Musaev F.T; Ergashev A.A (Zien Journals, 2023)
This article highlights the work devoted to the specifics of the course, management of patients with chronic pulmonary disease.
Keywords: COPD; withtarmic age; bronchopulmonary system